(untitled) (Research, Society and Development, 2026)
Introduction: Seizures are one of the most frequent neurological emergencies in emergency departments, requiring rapid recognition and appropriate management to prevent complications such as hypoxia, secondary brain injury, and progression to status epilepticus. The aim of this study is to understand seizures and their management in the emergency department. Methodology: This is an integrative literature review conducted in the PubMed, Virtual Health Library (VHL), and Google Scholar databases. Results and Discussion: The studies analyzed demonstrate that the management of seizures should follow a systematized approach, prioritizing stabilization of the airway, breathing, and circulation, followed by the early use of benzodiazepines as first-line therapy. Anticonvulsants such as phenytoin, levetiracetam, and valproate are widely used as second-line therapy, with a growing trend towards the use of drugs with a better safety profile. Identifying the etiology of the seizure and stratifying the risk of recurrence are fundamental to guiding conduct and follow-up. The adoption of clinical protocols has shown a positive impact on reducing therapeutic failures and complications. Conclusion: It is concluded that the effective management of seizures in urgent and emergency care units depends on early recognition, the application of evidence-based protocols, and the training of healthcare teams. The appropriate approach contributes to better clinical outcomes and a reduction in associated morbidity and mortality.